Analisis Kepuasan Kerja terhadap Kinerja Karyawan di Warung Makan Pelem Asri - Afif Margi Lestari; Nurul Sulistya Ningsih; Suratin Suratin (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study aims to analyze the influence of job satisfaction on employee performance at Warung Makan Ayam Penyet Pelem Asri, Boyolali. The study used a qualitative method with a case study approach. Data collection was conducted through in-depth interviews with employees and the business owner, direct observation of work activities, and relevant documentation. The results showed that the level of employee job satisfaction is relatively high, formed from a combination of structural, social, physical, and psychological factors. These factors include clear division of tasks, a regular work shift system, harmonious interpersonal relationships between employees, and the availability of adequate work facilities and compensation. High job satisfaction has been shown to encourage intrinsic motivation, discipline, and consistency in carrying out employees' duties. This is reflected in the ability of employees to provide fast, friendly, and consistent service, especially during busy operating hours. The research findings confirm that job satisfaction has a significant influence on employee performance, which in turn impacts customer satisfaction and business sustainability. Therefore, management needs to maintain and improve factors supporting job satisfaction to maintain service quality and business competitiveness.